IT Strategic Planning pada AMIK XYZ tahun 2020-2024 - Dicky Pratama (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
Most organizations in all sectors of industry, commerce, non-profit and government are now fundamentally dependent on information systems (IS) and information technology (IT). SI and IT are required to be the key to operational activities in all fields, not just as a tool. Utilization of IS / IT aims to improve the effectiveness and efficiency of operational activities and produce benefits for the long term. One of the benefits of using IS/IT for the long term is to be able to bring organizations, companies and institutions to achieve competitive advantage. AMIK XYZ is a private university based on information technology. AMIK XYZ's vision is to become an excellent university in Indonesia in 2028, which has a high commitment to quality education. To achieve its vision, AMIK XYZ requires a portfolio of future applications that are expected to bring AMIK XYZ to competitive advantage. This information technology strategic planning adopts the Ward and Peppard framework. The models used in this study are Five Force Porters, Value Chain, SWOT Matrix, Critical Success Factor and Mc Farlan Strategic Grid. The stages in this research are primary and secondary data collection then an internal and external environment analysis is carried out, then an IS / IT strategy analysis is carried out, a gap analysis is carried out to determine the application to be developed and an improvement of existing features, for the creation of an IS / IT development roadmap. The results of IS / IT strategic planning are business strategies, IS / IT management strategies and future portfolio applications that are aligned with business strategies. The IS / IT strategy that will be the first priority to be developed is adjusted to the priority issues that must be addressed immediately. The implementation of future application portfolios is expected to bring AMIK XYZ to its vision.